Dzieło zamknięte księdza Mariana Wolniewicza, czyli nieznana liryka poznańskiego biblisty - Kubski, Grzegorz (Ecclesia. Studia z Dziejów Wielkopolski, 2011)
Rev. Prof. Marian Wolniewicz is one of the most outstanding contemporary biblical scholars of the Poznań theological milieu. From his youth until the end of his life (t 2005) he wrote personal lyric poetry. A selection of his poems was published posthumously by the Theological Faculty of Adam Mickiewicz University in a volume titled A Spiritual Diary in Verse edited by Feliks Lenort with an introduction by Zdzisław Grzegorski, a theologian and scholar of Polish literature. The poems predominantly express man's religious experience through impressions of the moment and feelings evoked by sights of the landscape, but the lyric subject does not define himself through realities characteristic of a priest and theologian. In his poetic attitude Rev. Marian Wolniewicz was inspired by the poetry of Wojciech Bąk and the French symbolists. Similarly to Stephane Mallarme he fulfilled the concepts of subsequent poems as a continuation of one single oeuvre which would finish with the death of the author. His last poetic notation was also his last attempt to translate a verse from the Gospel according to John.